2006
DOI: 10.1016/j.jcrs.2006.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Corneal-thickness spatial profile and corneal-volume distribution: Tomographic indices to detect keratoconus

Abstract: Corneal-thickness spatial profile, corneal-volume distribution, percentage increase in thickness, and percentage increase in volume were different between keratoconic corneas and normal corneas and could serve as indices to diagnose keratoconus and screen refractive candidates. Further studies are necessary to evaluate whether these tomographic indices are more sensitive and specific than the classic Placido-based topography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
262
4
29

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 403 publications
(311 citation statements)
references
References 43 publications
9
262
4
29
Order By: Relevance
“…They found statistically significant differences between groups in all positions of corneal-thickness spatial profile as well as in the percentage increase in thickness between 3.5 mm and 7.0 mm diameters. 24 These authors conclude that this pachymetric analysis could diagnose keratoconus and screen refractive candidates. In a study using the scanning-slit technology, Saad and Gatinel 75 found that indices generated from corneal thickness (percentage of thickness increase from the thinnest point to the periphery) and curvature measurements (percentage of variation of anterior and posterior curvatures) over the entire cornea centered on the thinnest point can identify very mild forms of ectasia undetected by a Placido-based neural network program.…”
Section: Pachymetric Analysis In Keratoconusmentioning
confidence: 90%
See 2 more Smart Citations
“…They found statistically significant differences between groups in all positions of corneal-thickness spatial profile as well as in the percentage increase in thickness between 3.5 mm and 7.0 mm diameters. 24 These authors conclude that this pachymetric analysis could diagnose keratoconus and screen refractive candidates. In a study using the scanning-slit technology, Saad and Gatinel 75 found that indices generated from corneal thickness (percentage of thickness increase from the thinnest point to the periphery) and curvature measurements (percentage of variation of anterior and posterior curvatures) over the entire cornea centered on the thinnest point can identify very mild forms of ectasia undetected by a Placido-based neural network program.…”
Section: Pachymetric Analysis In Keratoconusmentioning
confidence: 90%
“…23 These systems also allow the clinician to characterize the pachymetric distribution as well as the volume of the evaluated cornea, which have been shown to be useful for keratoconus diagnosis and characterization. 24 The aim of the current review is to summarize the diagnostic criteria defined for keratoconus with the more advanced topography systems, including analysis of the posterior corneal surface and pachymetric distribution. These criteria are especially useful for screening corneal refractive surgery candidates to avoid performing the surgical procedure in a pathological or potentially pathological cornea.…”
Section: J Cataract Refract Surg 2012; 38:2167-2183 Q 2012 Ascrs and mentioning
confidence: 99%
See 1 more Smart Citation
“…Nas últimas décadas, observou-se uma verdadeira revolução nos métodos diagnósticos em córnea, destacando-se o advento da topografia de reflexão dos discos de Placido (39,42) , tomografia com reconstrução 3-D (43)(44)(45)(46) , estudo biomecânico da córnea in vivo (47)(48)(49)(50)(51)(52) e a aberrometria ocular (53,59) . A análise da frente de onda (wavefront) ou aberrometria ocular total permite a caracterização das aberrações ópticas do olho de forma mais detalhada e complexa que a tradicionalmente realizada.…”
unclassified
“…A córnea é fisiologicamente mais fina no centro e mais espessa na sua periferia, com aumento gradual em direção ao limbo. O perfil de progressão paquimétrico é um parâmetro tomográfico da córnea que tem características paramétricas "Gaussianas" em uma população normal e tem características significativamente distintas em córneas normais e com ceratocone (16,17) . O tomógrafo de córnea e segmento anterior, Pentacam (Oculus) tem software específico que analisa graficamente a progressão paquimétrica e calcula a média de progressão para cada olho estudado.…”
unclassified